Current methodologies and implications of phase identification of the vertical jump: A systematic review and meta-analysis - Eagles , A. N.; Leigh Sayers, M. G.; Bousson, M.; Ingham Lovell, D. (Sports Medicine, 2015)
The vertical jump (VJ) is considered a key indicator of lower limb explosive strength. Previous research has established that rate of force development and time to peak force are linked closely to athletic ability and hence the ability to extract these accurately is of significance. Objectives: The objectives of this study were to (1) review the literature to ascertain what methods are currently used to extract jump phases from the force platform data and (2) compare identified methods on neutral data. Methods: In Part 1, an electronic search was conducted using PubMed, Central, and EBSCO host (January 1965 to April 2014). Articles were included if they (1) detailed how VJ phases from the force platform data were identified and (2) used only force platform data in the analysis. Additionally, study design and quality was independently examined. In Part 2, the three common methodologies identified were used to analyze a neutral pool of data to determine if any variance existed. Results: For Part 1, a total of 19 studies met the inclusion criteria. Meta-analysis determined three methods of phase identification used in the literature from which to extract force-time variables. In Part 2, a one-way analysis of variance and Scheffe`s post-hoc tests showed significant differences (p < 0.01) for force-time variables (eccentric phase time, concentric phase time, time to peak force, rate of force development) between methods. Conclusion: The results demonstrate that three common methods exist for determination of the VJ phases from force platform data. Consequently, each produce different values for force-time variables when used on a neutral data pool. There is a clear need for a robust agreed method for VJ analysis.